2014
DOI: 10.1080/13506285.2014.890689
|View full text |Cite
|
Sign up to set email alerts
|

Encoding the target or the plausible preview word? The nature of the plausibility preview benefit in reading Chinese

Abstract: Previous studies have shown that a plausible preview word can facilitate the processing of a target word as compared to an implausible preview word (a plausibility preview benefit effect) when reading Chinese (Yang, Wang, Tong, & Rayner, 2012; Yang, 2013). Regarding the nature of this effect, it is possible that readers processed the meaning of the plausible preview word and did not actually encode the target word (given that the parafoveal preview word lies close to the fovea). The current experiment examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
8
27
1
Order By: Relevance
“…However, there was no benefit from semantic relatedness, and the two factors did not interact, that is, the benefit to reading the target psycho , from the synonym preview insane was equivalent to that for the plausible but semantically unrelated preview modest. This finding was consistent with plausibility preview effects observed in Chinese (Yang, Wang, Tong, & Rayner, ; Yang, Li, Wang, Slattery, & Rayner, ) that had previously been assumed to be specific to its logographic writing system. Converging evidence for the plausibility preview effect in English was provided by Schotter and Jia () who found that synonym, antonym, and plausible unrelated previews all yielded benefits on first‐pass reading relative to implausible previews.…”
Section: Plausibility Preview Effectssupporting
confidence: 89%
“…However, there was no benefit from semantic relatedness, and the two factors did not interact, that is, the benefit to reading the target psycho , from the synonym preview insane was equivalent to that for the plausible but semantically unrelated preview modest. This finding was consistent with plausibility preview effects observed in Chinese (Yang, Wang, Tong, & Rayner, ; Yang, Li, Wang, Slattery, & Rayner, ) that had previously been assumed to be specific to its logographic writing system. Converging evidence for the plausibility preview effect in English was provided by Schotter and Jia () who found that synonym, antonym, and plausible unrelated previews all yielded benefits on first‐pass reading relative to implausible previews.…”
Section: Plausibility Preview Effectssupporting
confidence: 89%
“…Consistent with previous evidence of a plausibility preview benefit (Schotter & Jia, 2016;Yang et al, 2014), the effect did not extend to total fixation duration because the early benefit for plausible previews was counteracted by a higher rate of regressions to the target after a plausible than after an implausible preview, even though the plausible previews were always compatible with the posttarget text. Thus, plausible previews yield a trade-off between shorter fixation durations during first-pass reading, but longer second-pass reading.…”
Section: Discussionsupporting
confidence: 74%
“…The results showed that, when the plausibility of the preview word in the sentence was controlled, no effect of preview-target semantic relatedness on fixation durations emerged. However, preview plausibility had a strong facilitative effect on firstpass reading measures of the target word (see also Schotter & Jia, 2016;Yang, Li, Wang, Slattery, & Rayner, 2014). These data demonstrate that preview benefit depends, in part, on the compatibility of the preview with the context.…”
Section: Text Comprehensionmentioning
confidence: 99%
“…However, it may be possible (and the comparison between the foveal and parafoveal disappearing text studies suggests) that in some cases parafoveal information itself is used for reading, potentially without the involvement of or need for foveal information. Indeed, recent research using the boundary paradigm has found evidence for preview benefit from a preview word that was completely unrelated to the target word, so long as the preview itself was a sensible word in the preceding sentence context (Schotter & Jia, 2016; Veldre & Andrews, 2016; Yang, Li, Wang, Slattery, & Rayner, 2014; Yang, Wang, Tong, & Rayner, 2012). …”
Section: Introductionmentioning
confidence: 99%